§ 1.

      8. f(x)   g(x) = ,
:
 
8.01.

f(x) = 36 2x5 + 5x4 27x3 + 2x2 5, g(x) = x 2;

8.02.

f(x) = 36 18x5 + 43x4 53x3 + 35x2 10 + 2, g(x) = x 1;

8.03.

f(x) = 6 ix5 + 2x4 + 3ix3 x2 + 2ix + 1 + i, g(x) = x + i;

8.04.

f(x) = 26 x5 + 2x3 x2 + x + 1, g(x) = x 2;

8.05.

f(x) = 26 x5 + 3x4 4x3 + x2 2x + 1, g(x) = x 3;

8.06.

f(x) = 6 + 2x5 12x4 + 30x3 80x 10, g(x) = x 3;

8.07.

f(x) = 6 7x5 8x4 + 450x2 + 2500x 12000, g(x) = x 5;

8.08.

f(x) = 27 ix4 + 3x2 + (3 i)x + 6, g(x) = x 2i;

8.09.

f(x) = 25 x4 + 3x2 x + 6, g(x) = x 1;

8. 10.  

f(x) = 25 + 7x4 8x2 + 3x 5, g(x) = x + 2;

8.11.

f(x) = 36 2x5 + x4 + 2, g(x) = x + 1;

8.12.

f(x) = 5 9x4 + 28x3 36x2 + 27x 27, g(x) = x 3;

8.13.

f(x) = 25 7x3 + x2 + 2x 5, g(x) = x + 2;

8.14.

f(x) = 26 7x5 + ix3 + (1 + i)x2 + 4x 4i, g(x) = x + 2i;

8.15.

f(x) = 5 2x4 + 3x2 4x + 2, g(x) = x 3i;

8.16.

f(x) = 46 x5 + 2x4 3x2 + 6, g(x) = x + 4;

8.17.

f(x) = x5 + 2x4 x3 + 2x2 1, g(x) = x 2;

8.18.

f(x) = x5 + 4x4 + 7x3 + 7x2 + 4x + 1, g(x) = x 1;

8.19.

f(x) = 25 9x4 + 29x3 56x2 + 63x 30, g(x) = x 3;

8.20.

f(x) = 2x5 + x4 2x3 x2 + x + 2, g(x) = x 2;

8.21.

f(x) = 6 x5 + 2x4 x3 x 4, g(x) = x i;

8.22.

f(x) = 26 + x5 x4 3x2 + 5, g(x) = x + i;

8.23.

f(x) = 35 + x4 x3 + 2x2 x + 1, g(x) = x 2;

8.24.

f(x) = 5 3x4 + x3 + 2x2 + 4x 2, g(x) = x 1;

8.25.

f(x) = 25 x4 3x3 + x 3, g(x) = x 1;

8.26.

f(x) = 6 2x4 + x3 + 4x2 8x + 4, g(x) = x i;

8.27.

f(x) = 2x5 2x4 + x3 + 3x2 1, g(x) = x + 3;

8.28.

f(x) = x5 4x4 + 3x2 x + 15, g(x) = x 2;

8.29.

f(x) = 2x5 x4 + 3x3 10x 10, g(x) = x 4;

8. 30. 

f(x) = 2x5 3x3 x2 ix + 3, g(x) = x 2i;

8.31.

f(x) = 6 2x5 + ix4 + 3x3 2x 4, g(x) = x + 2i;

8.32.

f(x) = 26 3x4 2x3 + 4x2 3x 6, g(x) = x + 4;

8.33.

f(x) = 35 2x3 3x2 + 4x + 3, g(x) = x + 5;

8.34.

f(x) = 6 (1 + i)x5 + 3x4 ix3 + 2x2 3x 1, g(x) = x + 3i;

8.35.

f(x) = 6 3x5 + 2x3 4x2 + 3x 5, g(x) = x 3;

8.36.

f(x) = 26 ix4 + 3x3 + (1 i)x2 + 2x 3, g(x) = x 3i.

\..\

                              Copyright © 2008-2009 ..   . .